TRANSITION OF THE ENGINE POWERED AIR-CONDITIONING SYSTEM TO THE SOLAR POWERED AIR-CONDITIONG SYSTEM IN A BUS: A FEASIBILITY STUDY - Yusoff, Zulpattah; Chew, Boon Cheong (Journal of Technology Management and Business, 2014)
Developing and generating a better way of the fossil fuel exertion is necessary in today’s transportation technology. Fossil fuels are of great importance in transport systems because they can be burned and producing significant amounts of energy to move the vehicle along. Generally usage of the air-conditioning system in the transportation will increase the usage of the fossil fuel, since the fuel is used to power the air-conditioning system, as well as to power the movement of the vehicle. The additional energy resource such as solar can be used in a vehicle to generate adequate energy to power the air-conditioning system. The research was grounded on an exploratory study. A qualitative case study approach was adopted. The data collected was analyzed to get the most efficient way to install the solar panel on a roof top of a bus. As the conclusion, the solar application will be benefit to a bus. The consumption of the fossil fuel is lowered and the efficiency of the engine is enhanced since the energy input is maximizing for the movement of the bus alone. Besides, this application also benefits to the environment as it produces lower carbon.